Insights into the development of lentigo maligna and dysplastic nevi: spotlight on the possible relation with sartans, thiazides and nitrosamines - Georgi Tchernev; Lorraine Joseph Kandathil; Nikhil Oliveira (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Since the alarming, yet prudent publication of the possible association of sartan use and development of various cancers in 2010, anti-hypertensive drugs (sartans and thiazide diuretics) have been closely monitored by various scientific and drug authoritarian bodies around the world. Fast forward 12 years, the number of scientific publications showing an increased risk of developing various types of cancer, including skin cancers, after sartan and/ or hydrochlorothiazide use is on the rise. Case description: A 77-year-old male with arterial hypertension under treatment for approximately 3 years (2018-2022) with three different preparations containing sartans in combination with hydrochlorothiazide was observed with a pigmented lesion present on the left cheek for 2 years with clinical and dermatoscopic suspicion of lentigo maligna, confirmed by histopathology. Further three suspected dysplastic naevi were also identified on the back, two of them confirmed by histopathology. Possible drug-induced melanocytic lesions were suspected and his drug regimen was changed. The prognosis was favorable with a good post-operative outcome. Conclusion: The amount of data linking the use of hydrochlorothiazide alone or in combination with sartans and the development of melanomas or their precursors, is worrying. Given the additional disclosure of pharmaceutical companies about the existing elevated concentrations of nitrosamines in these two classes of antihypertensive drugs, the establishment of a causal relationship between the intake of a particular carcinogen and the development of a tumor or tumor precursor requires careful and detailed scrutiny. The extent to which sartan/hydrochlorothiazide used and the occurrence of the lentigo maligna, especially when shared data points in this direction, remains unclear. However, in clinical practice, it should be highly recognized.